Proceedings 7th International Oat Conference - (:unkn) unknown (MTT, 2004)
At the 6th International Oat Conference, held in New Zealand, in 2000, it was agreed that the next conference would be held in Helsinki, Finland, in 2004. The National Organising Committee of the forthcoming conference gave a warm welcome to the important task devoted to oats. With the conference theme, Born to be functional, the National Organising Committee aspired to emphasise the essence of oat as a crop - the thorough functionality we have experienced in oats in large context. The Conference Program and Proceedings cover the following main areas with titles: Born to be functional; Genetic resources; Breeding and biotechnology (quality, yield and resistance); Markets, products and applications (feed, food and non-food) and Production chain. This proceedings is a compilation of eight short papers written by keynote speakers, and 140 abstracts of oral and poster presentations.
Keywords: Ka; funktionaalisuus; non food; satofysiologia; sovellutukset; kaura; prosessointi; rehu; ruoka; geenivarat; kasvinjalostus; bioteknologia; laatu; sato; kestävyys; tuotanto; viljely; markkerit; tuotteet; Avena sp.; oat; functionality; processing; feed; food; non-food; genetic resources; plant breeding; biotechnology; quality; yield; resistance; production; crop physiology